Method for predicting maximum dispersion concentration of molybdenum disulfide nanosheet in polar solvent

By predicting the highest dispersion concentration of molybdenum disulfide nanosheets in polar solvents, the problems of dispersion and performance in composite materials are solved, and the controllable dispersion and performance of nanosheets in composite materials are achieved.

CN119845801AActive Publication Date: 2025-04-18ZHEJIANG UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510172462.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-18
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

Molybdenum disulfide nanosheets are prone to agglomeration in solvents, affecting their dispersion and properties in composite materials, and it is difficult for the prior art to accurately determine their highest dispersion concentration in solvents.

Method used

By obtaining the highest dispersion concentration of molybdenum disulfide nanosheets in different polar solvents, their surface tension is calculated, and a linear relationship model is constructed based on the surface tension to predict their highest dispersion concentration in the target polar solvent.

Benefits of technology

The controllable dispersion of molybdenum disulfide nanosheets in composite materials is achieved, which maximizes its performance and promotes its widespread promotion in industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119845801A_ABST
    Figure CN119845801A_ABST
Patent Text Reader

Abstract

The invention provides a method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in polar solvents, which comprises the following steps: dispersing molybdenum disulfide nanosheets in polar solvents with different surface tensions, and calculating the surface tensions of the molybdenum disulfide nanosheets by using an OWRK theory. By comparing the difference between the surface tension of the polar solvent and the surface tension of the molybdenum disulfide nanosheet, a linear relation model of the highest dispersion concentration and the surface tension difference value is established, and the method can accurately predict the highest dispersion concentration of the molybdenum disulfide nanosheet under the condition of the polar solvent. And the surface tension of the solvent is adjusted through the compound solvent so as to optimize the dispersity of the nanosheet, so that the photoelectric performance, the catalysis performance and the like of the material are improved, the industrial application value is relatively high, a theoretical basis can be provided for controllable dispersion and large-scale production of a nano material, and the research, development and production efficiency of the material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nano material dispersion, and in particular to a method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in a polar solvent. Background Art

[0002] Molybdenum disulfide (MoS2) nanosheets, as a typical two-dimensional transition metal dichalcogenides (TMDCs), are widely used in photoelectric conversion, catalytic reaction, energy storage, sensor technology and high-performance nanocomposites due to their excellent electronic properties, optical properties and lubricity. In particular, single-layer MoS2 nanosheets, due to their ultra-high specific surface area and significant size effect, can significantly improve the overall performance of the material when incorporated into a matrix such as a polymer in trace amounts, and therefore become an important choice for high-efficiency performance enhancers.

[0003] However, the ultra-high specific surface area of ​​MoS2 nanosheets also makes it easy for them to have strong mutual attraction between particles in the dispersion medium, which leads to agglomeration. This agglomeration will not only affect the properties of the MoS2 nanosheets themselves, but also have a negative impact on the overall performance of the final material, especially in application scenarios where high dispersibility and stability need to be ensured. In order to give full play to the excellent photoelectric, catalytic and other properties of MoS2 nanosheets in composite materials, it is necessary to ensure that they remain in a single layer or uniformly dispersed in the solvent or matrix. However, when the content of nanosheets is too high, the dispersibility is often severely affected and leads to agglomeration, which makes it impossible to maximize the performance of the nanosheets. Therefore, the maximum dispersible concentration of MoS2 nanosheets in the solvent becomes a key technical issue.

[0004] In the Chinese patent document CN117025054A "An anticorrosive coating of a molybdenum disulfide-epoxy hydrophobic coating and its preparation method", it is intended to enhance the hydrophobic properties of epoxy resin coatings by adding molybdenum disulfide nanosheets. However, due to the agglomeration and stacking of nanosheets, the coating surface is uneven, and pores and cracks of different sizes will appear after drying, affecting the overall quality of the coating. Similarly, the Chinese patent document CN114836097A "A multifunctional nano-architectural exterior wall coating and its preparation method" has developed an exterior wall coating with mildew resistance and high mechanical strength, but the ratio of water, ethanol and polyvinyl pyrrolidone needs to be continuously regulated during the preparation process to ensure the uniform dispersion of molybdenum disulfide nanosheets in the solvent, which leads to the difficulty in controlling the dispersion concentration of nanosheets and affects the performance stability of the material. Therefore, there is currently a lack of an effective method to accurately determine the maximum dispersion concentration of nanomaterials in solvents, and this concentration is crucial for the controllable dispersion of nanomaterials. Solving this problem can not only ensure the uniform dispersion of nanosheets in composite materials and maximize their performance, but also promote the widespread promotion of MoS2 nanosheets in industrial applications.

[0005] In summary, predicting the highest stable dispersion concentration of MoS2 nanosheets in solvents and effectively regulating their dispersibility are crucial to ensure their full performance and application, and have become key technical challenges in achieving large-scale application of MoS2 nanosheets. Summary of the invention

[0006] The purpose of the present invention is to provide a method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in polar solvents, which can predict the maximum dispersion concentration of molybdenum disulfide nanosheets in different polar solvents based on surface tension, and is of great significance for achieving controllable dispersion of molybdenum disulfide nanosheets in composite materials and their industrial application.

[0007] To achieve the above objectives, the present technical solution provides a method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in a polar solvent, comprising the following steps:

[0008] (1) obtaining the highest dispersion concentration of MoS2 nanosheets in at least two polar solvents with different surface tensions;

[0009] (2) Calculate the surface tension of MoS2 nanosheets;

[0010] (3) A linear relationship model is constructed based on the surface tension of the polar solvent, the surface tension of the MoS2 nanosheets, and the maximum dispersion concentration of the MoS2 nanosheets in the corresponding polar solvent;

[0011] (4) Predict the maximum dispersion concentration of MoS2 nanosheets in the target polar solvent based on the linear relationship model.

[0012] According to the preferred embodiment of the present invention, in step (1), the molybdenum disulfide nanosheets are microscopically sized from 1 to 10 6 nm, and nanosheets with a thickness of 0.5 to 100 nm.

[0013] Preferably according to the present invention, in step (1), the molybdenum disulfide nanosheets are single-layer or few-layer molybdenum disulfide nanosheets of 2H phase, 1T phase and 3R phase.

[0014] Preferably, in step (1), the molybdenum disulfide nanosheets are uniformly dispersed in a polar solvent to obtain a maximum dispersion concentration. Preferably, the molybdenum disulfide nanosheets are uniformly dispersed in the polar solvent by ultrasound or stirring.

[0015] Preferably, according to the present invention, in step (1), the polar solvent is selected from one or more of the following complex solvents: water, isopropyl alcohol (IPA), ethanol (EtOH), N-methylpyrrolidone (NMP), 1,4-butanediol (BDO), and ethylene glycol (EG).

[0016] According to the preferred embodiment of the present invention, in step (1), the surface tension of the polar solvent is 10 to 80 mJ / m 2 .

[0017] Preferably, according to the present invention, in step (1), molybdenum disulfide nanosheets are uniformly dispersed in a polar solvent to obtain a dispersion, the dispersion having an initial concentration of 0 to 100 g / L is centrifuged and the concentration of the supernatant after centrifugation is tested, and the maximum dispersion concentration at which the molybdenum disulfide nanosheets are stably dispersed in the corresponding polar solvent is determined based on the relationship between the initial concentration of the dispersion and the concentration of the supernatant after centrifugation.

[0018] Preferably, according to the present invention, in step (1), the centrifugal conditions for centrifuging the dispersion with an initial concentration of 0 to 100 g / L are: a centrifugal force range of 10 to 1200 g, and a centrifugal time of 5 to 30 minutes.

[0019] Preferably, according to the present invention, in step (1), a concentration change relationship graph is drawn with the initial concentration of the dispersion as the horizontal coordinate and the concentration of the supernatant after centrifugation as the vertical coordinate, and the slope change of the concentration change relationship graph is observed, and the maximum dispersion concentration of molybdenum disulfide nanosheets stably dispersed in the corresponding polar solvent is determined based on the slope change.

[0020] According to the present invention, preferably, in step (1), the concentration of the supernatant after centrifugation corresponding to the time when the initial concentration of the dispersion liquid and the concentration of the supernatant after centrifugation become negatively correlated is taken as the maximum dispersion concentration of the molybdenum disulfide nanosheets stably dispersed in the corresponding polar solvent. In other words, the concentration of the supernatant after centrifugation corresponding to the time when the slope of the concentration change relationship graph becomes a negative value is taken as the maximum dispersion concentration of the molybdenum disulfide nanosheets stably dispersed in the corresponding polar solvent.

[0021] Preferably, according to the present invention, in step (2), the molybdenum disulfide nanosheets are made into a film, and the polar solvent same as that in step (1) is dropped on the film to measure the contact angle, and the surface tension of the molybdenum disulfide nanosheets is calculated based on the intrinsic properties of the polar solvent and the contact angle.

[0022] Preferably, according to the present invention, the OWRK theory is combined with Young's equation to obtain the following related equation:

[0023] 0.5(1+cosθ)γ L / (γ d,L ) 1 / 2 =(γ p,S ) 1 / 2 ·(γ p,L / γ d,L ) 1 / 2 +(γ d,S ) 1 / 2 ;

[0024] Where θ is the contact angle, γ L ,γ d,L ,γ p,L It is an intrinsic property of polar solvents;

[0025] The surface tension component γ of the MoS2 nanosheets was obtained based on the slope and intercept of the fitting graph. d,s ,γ p,s , the sum of the surface tension components is taken as the surface tension of MoS2 nanosheets.

[0026] About drawing the fitting graph: p,L / γ d,L ) 1 / 2 As the horizontal axis, 0.5(1+cosθ)γ L / (γ d,L ) 1 / 2 As the ordinate, draw a fitting graph, and take the square value of the slope a on the fitting graph as the first surface tension component γ d,s , take the square value of the intercept b on the fitting graph as the second surface tension component γ p,s , the surface tension of MoS2 nanosheets is calculated based on the first surface tension component and the second surface tension component:

[0027] γ S =γ p,S +γ d,S =a 2 +b 2 ;

[0028] where γ p,L is the polar component of the surface tension of the polar solvent, γ d,L is the dispersion component of the surface tension of the polar solvent, γ L is the surface tension of the polar solvent, γ p,s is the polar component of the surface tension of MoS2 nanosheets, γ d,s is the dispersion component of the surface tension of MoS2 nanosheets, γ s is the surface tension of MoS2 nanosheets, and θ is the contact angle of polar solvents with different surface tensions on the surface of MoS2 nanosheets.

[0029] Preferably, according to the present invention, in step (2), the molybdenum disulfide nanosheets are pressed or filtered to prepare a film, and the polar solvent same as that in step (1) is dropped on the film to measure and obtain the contact angle.

[0030] Preferably according to the present invention, in step (2), the droplet volume of the polar solvent used to test the contact angle is 0.5-10 μL.

[0031] Preferably, according to the present invention, in step (3), the tension difference between the surface tension of the polar solvent and the surface tension of the molybdenum disulfide nanosheets is calculated, and a fitting graph is drawn with the absolute value of the tension difference as the horizontal coordinate and the highest dispersed concentration of the molybdenum disulfide nanosheets in the corresponding polar solvent as the vertical coordinate, and a linear relationship model is constructed based on the fitting graph.

[0032] Preferably, according to the present invention, the linear relationship model represents the surface tension difference-maximum dispersion concentration relationship between the tension difference and the maximum dispersion concentration, wherein the intercept value represents the maximum dispersion concentration that the molybdenum disulfide nanosheets can reach in the polar solvent.

[0033] According to the preferred embodiment of the present invention, the surface tension difference between the polar solvent and the surface tension of the molybdenum disulfide nanosheets is controlled to be 0 to 50 mJ / m 2 .

[0034] Preferably, according to the present invention, in step (4), the tension difference between the target polar solvent and the surface tension of the molybdenum disulfide nanosheets is calculated, and the maximum dispersion concentration of the molybdenum disulfide nanosheets in the current target polar solvent is calculated based on the tension difference and the linear relationship model.

[0035] Compared with the prior art, this technical solution has the following characteristics and beneficial effects:

[0036] (1) The present invention provides a method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in polar solvents to predict the maximum stable dispersion concentration of molybdenum disulfide nanosheets in the preparation process of composite materials. The present invention uses the absolute value of the tension difference between the surface tension of polar solvents with different surface tensions and the surface tension of molybdenum disulfide nanosheets as the horizontal coordinate, and the maximum dispersion concentration of molybdenum disulfide nanosheets in polar solvents with different surface tensions as the vertical coordinate, and draws a graph to fit to obtain a linear relationship, that is, the absolute value of the surface tension difference-maximum dispersion concentration relationship. In the actual industrial production process, the required solvent surface tension value can be substituted into the relationship to obtain the maximum concentration of molybdenum disulfide nanosheets dispersed therein, thereby improving R&D and production efficiency and laying a foundation for the controllable dispersion and large-scale application of molybdenum disulfide nanosheets.

[0037] (2) The method of the present invention can not only be used to determine the maximum dispersion concentration of molybdenum disulfide nanosheets in a solvent, but also can be used to more quickly obtain a suitable and stable dispersion concentration of nanofillers when other nanofillers are used in the production process. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Photos showing the 2H phase molybdenum disulfide nanosheets of Example 1 of the present invention dispersed in a series of polar solvents with different surface tensions.

[0039] Figure 2The test results of the highest stable dispersion concentration of 2H phase molybdenum disulfide nanosheets in water according to Example 1 of the present invention are shown.

[0040] Figure 3 The contact angle test photos of different polar solvents on the surface of 2H phase molybdenum disulfide nanosheets in Example 1 of the present invention are shown.

[0041] Figure 4 The surface tension process calculation fitting diagram of the 2H phase molybdenum disulfide nanosheets of Example 1 of the present invention is shown.

[0042] Figure 5 The graph showing the relationship between the maximum dispersion concentration and the surface tension difference of the 2H phase molybdenum disulfide nanosheets in Example 1 of the present invention is shown.

[0043] Figure 6 A graph showing the highest dispersion concentration of 2H phase molybdenum disulfide nanosheets in Verification Example 1 of the present invention in a target solvent is shown.

[0044] Figure 7 The photographs show that the 1T phase molybdenum disulfide nanosheets of Example 2 of the present invention are dispersed in a series of polar solvents with different surface tensions.

[0045] Figure 8 The test photographs of the contact angles of different solvents on the surface of 2H phase molybdenum disulfide nanosheets according to Example 2 of the present invention are shown.

[0046] Fig. 9 A calculation fitting diagram of the surface tension process of 1T phase molybdenum disulfide nanosheets of Example 2 of the present invention is shown.

[0047] Fig.10 A relationship diagram between the maximum dispersion concentration and the surface tension difference of 1T phase molybdenum disulfide nanosheets of Example 2 of the present invention is shown.

[0048] Fig.11 A graph showing the maximum concentration of 1T phase molybdenum disulfide nanosheets dispersed in a target solvent according to Verification Example 2 of the present invention is shown. DETAILED DESCRIPTION

[0049] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0050] Embodiment 1

[0051] (1) 0.01 g of 2H-phase MoS2 nanosheets (thickness ∼1 nm) were dispersed uniformly in 10 mL of water by ultrasound to obtain an aqueous dispersion of 2H-MoS2, wherein the concentration of 2H-MoS2 was 1 g / L. The initial concentration c was prepared in the same manner. in The aqueous dispersion is 0.10-4.00 g / L. The aqueous dispersion is centrifuged (RCF is 1000 g) for 10 min and the supernatant is taken to test the concentration c of 2H-MoS2 re . With c in is the horizontal axis, corresponding to c re Plotting the ordinate gives Figure 2 , observe the slope change, at c in When it is 3.0g / L, the slope becomes negative. At this time, c re The maximum dispersion concentration of 2H phase MoS2 nanosheets in water is 1.6 g / L. The dispersion state is shown in the following figure. Figure 1 shown.

[0052] Using the same method as above, the highest dispersion concentrations of 2H-MoS2 in IPA, EtOH, NMP, BDO, and EG were 0.4 g / L, 0.4 g / L, 7.6 g / L, 9.8 g / L, and 10.6 g / L, respectively. The dispersion state photos are shown in Figure 1 shown.

[0053] (2) The 2H-MoS2 nanosheets were pressed and the contact angles of water, IPA, EtOH, NMP, and EG on their surfaces were tested. The drop volume was 1 μL. The contact angle data are shown in Figure 2. Figure 3 shown.

[0054] According to the Owen, Wendt, Rabel, and Kaelbl (OWRK) theory, combined with Young's equation, the intrinsic properties of the solvent (γ L ,γ d,L ,γ p,L ) and contact angle (θ):

[0055] 0.5(1+cosθ)γ L / (γ d,L ) 1 / 2 =(γ p,S ) 1 / 2 ·(γ p,L / γ d,L ) 1 / 2 +(γ d,S ) 1 / 2 ;

[0056] With (γ p,L / γ d,L ) 1 / 2is the horizontal axis, 0.5(1+cosθ)γ L / (γ d,L ) 1 / 2 The slope a and intercept b are obtained by fitting the graph; the surface tension value γ of 2H-MoS2 nanosheets is obtained according to the following formula s ;

[0057] γ S =γ p,S +γ d,S =a 2 +b 2 ;

[0058] Among them, γ p,L is the polar component of the surface tension of the polar solvent, γ d,L is the dispersion component of the surface tension of the polar solvent, γ L is the total surface tension of the polar solvent, γ p,s is the polar component of the surface tension of 2H-MoS2, γ d,s is the dispersion component of the surface tension of 2H-MoS2, γ s is the total surface tension of 2H-MoS2, and θ is the contact angle of solvents with different surface tensions on the surface of 2H-MoS2.

[0059] The γ corresponding to the five polar solvents was calculated by the same method. p,L , γ d,L , γ L The contact angle data are shown in Table 1 below:

[0060] Table 1 Contact angle data in solvents of different polarity

[0061] Polar solvents <![CDATA[γ L (mJ / m 2 )]]> <![CDATA[γ p,L (mJ / m 2 )]]> <![CDATA[γ d,L (mJ / m 2 )]]> θ(°) water 72.8 50.7 22.1 55.6±8 EG 47.7 21.4 26.3 45.0±5 NMP 40.8 11.6 29.2 34.9±1 EtOH 23.7 4.4 19.3 13.1±3 IPA 23 3.5 19.5 6.6±1

[0062] Calculate γ d,s 5.7mJ / m 2 ,γ p,s 43.0mJ / m 2 , according to γ s =γ p,s +γ d,s The surface tension of 2H-MoS2 is 48.7 mJ / m 2 .

[0063] (3) Calculate the absolute value of the difference between the surface tension of water, IPA, EtOH, NMP, BDO, and EG and the surface tension of 2H-MoS2 nanosheets, use this as the horizontal axis, and use the highest stable dispersion concentration in different solvents as the vertical axis for linear fitting, such as Figure 5 As shown, it basically conforms to the linear relationship, and the linear relationship C is obtained max = -0.4|Δγ|+11.0;

[0064] (4) In the actual industrial production process, the desired target solvent surface tension value can be substituted into this relationship to obtain the maximum concentration of 2H-MoS2 nanosheets dispersed therein, laying the foundation for the controllable dispersion and large-scale application of 2H-MoS2 nanosheets.

[0065] Verification Example 1

[0066] The target solvent is obtained by compounding water and ethanol, wherein the volume fraction of ethanol is 75%. According to the method of step (1) of Example 1, the maximum dispersion concentration of 2H-MoS2 nanosheets (thickness of ~1nm) in the target solvent is determined to be 3.6g / L.

[0067] The surface tension of the target solvent is 29.8 mJ / m 2 The difference between the surface tension of 2H-MoS2 nanosheets and that of 2H-MoS2 nanosheets is 18.9 mJ / m 2 Then substitute the above difference into the relationship determined in Example 1, as Figure 6 As shown, the calculated maximum stable dispersion concentration is 3.7 g / L.

[0068] From the above comparison, it can be seen that the method of the present invention can accurately determine the maximum dispersion concentration of 2H phase molybdenum disulfide nanosheets in the target solvent.

[0069] Example 2

[0070] (1) The difference from Example 1 is that 1T phase MoS2 nanosheets are used to obtain the highest dispersion concentrations of 1T-MoS2 in IPA, EtOH, NMP, BDO, and EG of 0.04 g / L, 0.06 g / L, 1.8 g / L, 2.0 g / L, and 2.5 g / L, respectively. The dispersion state photos are shown in Figure 7 shown.

[0071] (2) 1T-MoS2 nanosheets were pressed and the contact angles of water, IPA, EtOH, NMP, and EG on their surfaces were tested. The drop volume was 1 μL. The contact angle data are shown in the figure. Figure 8 shown.

[0072] According to Owen, Wendt, Rabel, and Kaelble theory OWRK theory, combined with Young's equation, the intrinsic properties of the solvent (γ L ,γ d,L ,γ p,L ) and contact angle (θ):

[0073] 0.5(1+cosθ)γ L / (γ d,L ) 1 / 2 =(γ p,S) 1 / 2 ·(γ p,L / γ d,L ) 1 / 2 +(γ d,S ) 1 / 2 ;

[0074] With (γ p,L / γ d,L ) 1 / 2 is the horizontal axis, 0.5(1+cosθ)γ L / (γ d,L ) 1 / 2 As the ordinate, the slope a and intercept b are obtained by plotting the fitting graph; the surface tension value γ of 1T-MoS2 nanosheet is obtained according to the following formula s ;

[0075] γ S =γ p,S +γ d,S =a 2 +b 2

[0076] Among them, γ p,L is the polar component of the surface tension of the polar solvent, γ d,L is the dispersion component of the surface tension of the polar solvent, γ L is the total surface tension of the polar solvent, γ p,s is the polar component of the surface tension of 1T-MoS2, γ d,s is the dispersion component of the surface tension of 1T-MoS2, γ s is the total surface tension of 1T-MoS2 nanosheets, and θ is the contact angle of polar solvents with different surface tensions on the 1T-MoS2 surface.

[0077] The γ corresponding to the five polar solvents was calculated by the same method. p,L , γ d,L , γ L The contact angle data are shown in Table 2 below:

[0078] Table 2 Contact angle data in solvents of different polarity

[0079]

[0080]

[0081] Calculate γ d,s 4.9mJ / m 2 ,γ p,s 50.4mJ / m 2 , according to γ s =γ p,s +γ d,sThe surface tension of 1T-MoS2 is 55.3 mJ / m 2 .

[0082] (3) Calculate the absolute value of the difference between the surface tension of water, IPA, EtOH, NMP, BDO, and EG and the surface tension of 1T-MoS2 nanosheets, use this as the abscissa, and use the highest stable dispersion concentration in different solvents as the ordinate for linear fitting, as shown in the following example: Fig.10 As shown, it basically conforms to the linear relationship, and the relationship C is obtained max =-0.1|Δγ|+3.1.

[0083] (4) In the actual industrial production process, the desired target solvent surface tension value can be substituted into this relationship to obtain the maximum concentration of 1T-MoS2 nanosheets dispersed therein, laying the foundation for the controllable dispersion and large-scale application of 1T-MoS2 nanosheets.

[0084] Verification Example 2

[0085] The target solvent is obtained by compounding water and ethanol, wherein the volume fraction of ethanol is 75%. According to the method of step (1) of Example 1, the maximum dispersion concentration of 1T-MoS2 nanosheets (thickness of ~1nm) in the target solvent is determined to be 0.7g / L.

[0086] The surface tension of the target solvent is 29.8 mJ / m 2 The difference between the surface tension of MoS2 nanosheets and that of MoS2 nanosheets is 25.5 mJ / m 2 Then substitute the above difference into the relationship determined in Example 2, as Fig.11 As shown, the calculated maximum stable dispersion concentration is 0.6 g / L.

[0087] From the above comparison, it can be seen that the method of the present invention can accurately determine the maximum dispersion concentration of 1T phase molybdenum disulfide nanosheets in the target solvent.

[0088] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in a polar solvent, characterized in that: The following steps are involved: (1) obtaining the highest dispersion concentration of MoS2 nanosheets in at least two polar solvents with different surface tensions; (2) Calculate the surface tension of MoS2 nanosheets; (3) A linear relationship model is constructed based on the surface tension of the polar solvent, the surface tension of the MoS2 nanosheets, and the maximum dispersion concentration of the MoS2 nanosheets in the corresponding polar solvent; (4) Predict the maximum dispersion concentration of MoS2 nanosheets in the target polar solvent based on the linear relationship model.

2. The method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in a polar solvent according to claim 1, characterized in that: In step (1), the polar solvent is selected from one or more of water, isopropyl alcohol (IPA), ethanol (EtOH), N-methylpyrrolidone (NMP), 1,4-butanediol (BDO), and ethylene glycol (EG).

3. The method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in a polar solvent according to claim 1, characterized in that: In step (1), the surface tension of the polar solvent is 10 to 80 mJ / m 2 .

4. The method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in a polar solvent according to claim 1, characterized in that: In step (1), the molybdenum disulfide nanosheets are microscopically sized 1 to 10 6 The invention discloses a nanosheet having a diameter of 100 nm and a thickness of 0.5 to 100 nm, wherein the molybdenum disulfide nanosheet is a single-layer or a few-layer molybdenum disulfide nanosheet of a 2H phase, a 1T phase, and a 3R phase.

5. The method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in a polar solvent according to claim 1, characterized in that: In step (1), molybdenum disulfide nanosheets are uniformly dispersed in a polar solvent to obtain a dispersion, the dispersion having an initial concentration of 0 to 100 g / L is centrifuged and the concentration of the supernatant after centrifugation is tested, and the maximum dispersion concentration at which the molybdenum disulfide nanosheets are stably dispersed in the corresponding polar solvent is determined based on the relationship between the initial concentration of the dispersion and the concentration of the supernatant after centrifugation.

6. The method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in a polar solvent according to claim 1, characterized in that: In step (1), the concentration of the supernatant after centrifugation corresponding to the time when the initial concentration of the dispersion and the concentration of the supernatant after centrifugation become negatively correlated is taken as the maximum dispersion concentration of molybdenum disulfide nanosheets stably dispersed in the corresponding polar solvent.

7. The method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in a polar solvent according to claim 1, characterized in that: In step (2), the molybdenum disulfide nanosheets are made into a film, and the polar solvent used in step (1) is dropped on the film to measure the contact angle. The surface tension of the molybdenum disulfide nanosheets is calculated based on the intrinsic properties of the polar solvent and the contact angle.

8. The method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in a polar solvent according to claim 1, characterized in that: Combining the OWRK theory with Young's equation, we get the following related equations: 0.5(1+cosθ)γ L / (c d,L ) 1 / 2 =(γ p,S ) 1 / 2 ·(c p,L / c d,L ) 1 / 2 +(c d,S ) 1 / 2 ; Where θ is the contact angle, γ L ,γ d,L ,γ p,L It is an intrinsic property of polar solvents; The surface tension component γ of the MoS2 nanosheets was obtained based on the slope and intercept of the fitting graph. d,s ,γ p,s , the sum of the surface tension components is taken as the surface tension of MoS2 nanosheets.

9. The method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in a polar solvent according to claim 1, characterized in that: In step (3), the tension difference between the surface tension of the polar solvent and the surface tension of the molybdenum disulfide nanosheets is calculated, and a fitting graph is drawn with the absolute value of the tension difference as the horizontal coordinate and the highest dispersed concentration of the molybdenum disulfide nanosheets in the corresponding polar solvent as the vertical coordinate, and a linear relationship model is constructed based on the fitting graph.

10. The method for predicting the maximum dispersion concentration of molybdenum disulfide nanosheets in a polar solvent according to claim 1, characterized in that: In step (4), the tension difference between the target polar solvent and the surface tension of the molybdenum disulfide nanosheets is calculated, and the maximum dispersion concentration of the molybdenum disulfide nanosheets in the current target polar solvent is calculated based on the tension difference and the linear relationship model.

Citation Information

Patent Citations

  • Multifunctional nano building exterior wall coating and preparation method thereof

    CN114836097A

  • Anticorrosive coating of molybdenum disulfide-epoxy hydrophobic coating and preparation method of anticorrosive coating

    CN117025054A

  • Preparation method of magnetic layered molybdenum disulfide nanosheets

    CN103787417A

  • Method for measuring dispersion degree of carbon nanomaterial in polymer matrix using dynamic contact angle

    KR1020090087603A

  • Gas sensor comprising nanoparticles and manufacturing method of the same

    KR1020160014845A